FIBCD1 Binds Aspergillus fumigatus and Regulates Lung Epithelial Response to Cell Wall Components - Jepsen, Christine Schoeler; Dubey, Lalit Kumar; Colmorten, Kimmie B.; Moeller, Jesper B.; Hammond, Mark A.; Nielsen, Ole; Schlosser, Anders; Templeton, Steven P.; Sorensen, Grith L.; Holmskov, Uffe (Frontiers in Immunology, 2018)
Aspergillus fumigatus (A. fumigatus) is a ubiquitous fungus of clinical importance associated with development of various pulmonary diseases and allergic hypersensitivity reactions. It is protected against environmental stress by a cell wall that contains polysaccharides such as chitin. We previously demonstrated that fibrinogen C domain-containing protein 1 (FIBCD1) is a membrane-bound protein that binds chitin through a conserved S1 binding site and is expressed in intestinal epithelium and salivary glands. Here, we further localized FIBCD1 protein expression at the surface of bronchial and alveolar human lung epithelium, observed recognition of A. fumigatus cell wall with S1 site-independent recognition. We observed FIBCD1-mediated suppression of IL-8 secretion, mucin production, and transcription of genes associated with airway inflammation and homeostasis in FIBCD1-transfected lung epithelial cells. These modulations were generally enforced by stimulation with A. fumigatus cell wall polysaccharides. In parallel, we demonstrated a FIBCD1-mediated modulation of IL-8 secretion induced by TLR2, -4, and -5. Collectively, our findings support FIBCD1 as a human lung epithelial pattern recognition receptor that recognizes the complex A. fumigatus cell wall polysaccharides and modulates the lung epithelial inflammatory response by suppressing inflammatory mediators and mucins.